2018
DOI: 10.5152/tud.2017.67366
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body mimicking neoplasia of the renal pelvis on magnetic resonance imaging

Abstract: A 65-year-old male presented with an incidental magnetic resonance imaging (MRI) finding of a right renal pelvis (RP) tumor-like mass. He was subjected to nephrostomy tube (NT) placement due to hydronephrosis secondary to an impacted ureteral stone. NT was removed after successful Ho:YAG laser lithotripsy. Abdominal MRI performed 19 months later for another indication showed RP wall thickening/enhancement and an intrapelvic low-intensity linear structure presenting as a magnetic susceptibility artifact. He und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Four case reports revealed suture material as a foreign body in the ureters causing encrustation and calcification. 3,8,10,13 Case reports by Qublan et al and Mamoulakis et al revealed intrauterine contraceptive device as a foreign body both in the distal ureters. 3,12 Metallic clip was reported by 2 studies as a ureteral foreign including the highlighted case in figures below.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four case reports revealed suture material as a foreign body in the ureters causing encrustation and calcification. 3,8,10,13 Case reports by Qublan et al and Mamoulakis et al revealed intrauterine contraceptive device as a foreign body both in the distal ureters. 3,12 Metallic clip was reported by 2 studies as a ureteral foreign including the highlighted case in figures below.…”
Section: Resultsmentioning
confidence: 99%
“…Other symptoms reported were flank pain, 3-5,10,11 followed by dysuria, 2,5,8,12 along with two incidental findings from imaging. 1,13 A total of 10/14 of the case reports, (Figure 3 and 4) 2,5-10,13 highlighted ureteroscopy + holmium laser fragmentation of calcification along with grasping forceps for retraction of foreign body . Li et al reported a laparoscopic left nephroureterectomy for a nonfunctioning kidney after lodging an intrauterine contraceptive device in the left distal ureter for 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations